Development of PAI Learning Media Using Artificial Intelligence Wordwall to Improve Student Learning Motivation in Class 1A of SMPN 8 Kota Bima - Ainun Sa'biah; Khairuddin Khairuddin; Irwan Irwan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
With the current technological developments, many artificial intelligence (AI) have been created that are useful as interactive learning media. Therefore, to avoid boredom and lack of interest in learning possessed by students if the learning media used is too monotonous and unpleasant to be applied to the learning process. So it is necessary to develop integrated and innovative learning media based on digital technology, for example by using artificial intelligence wordwall as a learning media. This type of research is development (R & D) using the ADDIE model. The results of the study show that starting from analysis, design, development, implementation, and evaluation are carried out in accordance with the ADDIE development model procedures. The learning interest shown when developing learning media appears to increase by an average of 84% with media feasibility after product validation with an average of 88% and with the practicality of using this wordwall learning media with an average of 85% and the development of PAI learning media using this wordwall was carried out in class 1A SMPN 8 Kota Bima.